Norwegian Design Principle for High Pressure Tunnels and Shafts: Its Applicability in the Himalaya - Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Cost effective, safe and long term sustainable hydropower development is key for the lasting economic growth in the Himalayan region. Increasing pressure towards the use of renewal and environmentally friendly energy for industrial growth and daily household use will force the Himalayan region to exploit hydropower energy more extensively. The traditionally used design approach of fully lined underground waterway system is costly and financially unfeasible as well as an obstacle to attract investment in the hydropower sector in the Himalaya. Hence, more innovative solutions are needed to make hydro generated energy more cost effective and as a sustainable energy solution in the long term. This paper briefly describes the geological set-up of Scandinavia, history of Norwegian Hydropower and reviews the design principle used to develop the underground waterway system in Norway. Brief comments are also made on the applicability of these principles in the Himalayan region. It is anticipated that more discussions will be made in the future on the geo-tectonic environment of the Himalaya and suitability of Norwegian design principle in the Himalayan region. DOI: http://dx.doi.org/10.3126/hn.v14i0.11254 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 14, 2014 January Page: 36-40